Pengaruh Promosi Dan Kemudahan Akses Terhadap Minat Belanja Pengguna Tiktok Shop Tebing Syahbandar - Maulana Ridho Pratama Damanik; Didik Gunawan; Willy Cahyadi (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to determine the influence of promotion and ease of access on the shopping interest of TikTok Shop users in Tebing Syahbandar. This research employs a quantitative descriptive approach. The study population consists of TikTok Shop users in Hamlet 3, Penggalangan Village, Tebing Syahbandar District. As the exact size of the population was unknown, the sample size was determined using Cochran's formula, resulting in 96.04, which was rounded to 96 respondents. Primary data sources were used; data were collected through questionnaires distributed to respondents and processed using SPSS 25 analysis software. The analysis results indicate that the first hypothesis is accepted, meaning the Promotion variable (X1) influences the shopping interest (Y) of TikTok Shop users in Tebing Syahbandar. The second hypothesis is accepted, meaning the Ease of Access variable (X2) influences the shopping interest (Y) of TikTok Shop users in Tebing Syahbandar. The third hypothesis is accepted, meaning the variables of Promotion (X1) and Ease of Access (X2) simultaneously influence the shopping interest (Y) of TikTok Shop users in Tebing Syahbandar.